A survey on the status of reference and information services in four high school libraries in Quezon City - Dery, Dorothy S. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1993)
This study analyzed the efficiency and effectiveness of Reference and Information Services of the high school libraries of Ateneo de Manila High School, Miriam College Foundation Incorporated High School, Philippine Science High School, and the University of the Philippines Integrated School. Using a questionnaire, it examined the date of establishment of the four high schools, number of student enrolment and faculty members during the School Year 1992-1993, location of the high school libraries, library collection, reference collection, type and number of reference queries, and library activities to encourage students and teachers to come to the library and use its resources, especially the reference materials.
Findings of the study revealed that all four high school libraries are well-equipped and have an adequate collection of books, periodicals, and other library materials so much needed for better library service to students and teachers.
Reference librarians of the four school libraries know and value the importance of information contained in all types of reference materials but some of them do not consider record-keeping of reference queries as an important aspect in the improvement of their respective Reference and Information Service.
Lastly, various library activities are organized by the four school librarians to encourage students and teachers to come to the library and use its resources.
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman
Keywords: High school libraries -- Information services. -- Philippines -- Quezon City; Reference services (Libraries) -- Philippines -- Quezon City